The Efficiency-Equity Frontier: Optimal Allocation of Village Funds In Indonesia's Decentralized Governance Framework - Wildan Maulana Assani Mualim; Ira Meiyenti; Arina Romarina; Ardieansyah Ardieansyah (Politeknik Siber Cerdika Internasional, 2026)
Background: Indonesia's Village Fund (Dana Desa) has disbursed Rp 608.9 trillion (≈ USD 35.8 billion) to 75,753 villages since 2015, yet whether this fiscal transfer simultaneously advances efficiency and equity in rural development remains an open empirical question. Spatial interdependencies among villages and heterogeneous local institutional capacities are rarely accounted for in existing evaluations. Objective: This study examines how Village Fund allocations navigate the efficiency–equity trade-off across Indonesian villages, quantifies spatial spillover effects on regional development outcomes, and develops evidence-based allocation algorithms to simultaneously advance efficiency and equity. Methods: We apply a Bayesian Spatial Durbin Model integrated with Generalized Random Forests to a balanced panel of 674,649 village-year observations (2015–2023). Identification draws on difference-in-differences with propensity score matching, regression discontinuity at population thresholds, and instrumental variables using pre-treatment geographic characteristics. Results: A 1% increase in Village Fund allocation reduces rural poverty by 0.152–0.183%, though this effect is contingent on local institutional capacity, with significantly larger gains among villages exceeding a capacity threshold of 0.65. Significant spatial spillovers (β = −0.089) indicate that investment in each village generates indirect poverty-reducing benefits for neighboring villages.The model explains 42.3% of outcome variation (R² = 0.423). Conclusions: The Village Fund considerably reduces rural poverty, but effectiveness is circumscribed by local institutional capacity—not merely village or fund size. Policymakers should prioritize capacity-building before scaling up allocations, and adopt performance-based formula adjustments that capitalize on spillover dynamics across village clusters.